Asfixia Event Based On LBW History And Early Children's Fertilizer - Maryne Hucek (Journal of Applied Nursing and Health, 2022)
Background: Asphyxia neonatal is a newborn condition that fails to breathe spontaneously and regularly immediately after birth. This condition is at risk of infant death, one of the causes of infant death. This study aimed to determine the relationship between LBW history and premature rupture of membranes with the incidence of asphyxia. Methods: The research design is case-control. The study population was all infants. The sample is a portion of babies totaling 64 respondents, using accidental sampling. The independent variable is infant weight and premature rupture of membranes. The dependent variable is the occurrence of asphyxia—statistical tests using Chi-Square with a <0.05. Results: The results showed that respondents had average birth weights, as many as 48 respondents (75%), had negative Premature rupture of membranes as many as 46 respondents (71.9%), and did not have Asphyxia as many as 44 respondents (68.8%). Statistical test between birth weight variables with asphyxia (p = 0,000 with Pearson chi-square 31,621) and between variables premature rupture of membranes with asphyxia (0,000 with chi-square 31,418) which means that the relationship between premature rupture of membranes and asphyxia is stronger than the relationship between birth weight with Asphyxia Conclusion: The greater the risk of premature rupture of membranes, the greater the likelihood of asphyxia, and the lower the birth weight, the greater the risk of asphyxia..